Work integrated learning experiences of primary health care post basic nursing students in clinical settings, a University of Technology context - Sibiya, MN (South African Journal of Higher Education, 2016)
This article explores and describes primary health care post-basic nursing students’ experience during clinical placements so as to address the challenges that are faced within the clinical settings. Work Integrated Learning (WIL), like in any other nursing course, is essential in primary health care education as required by the South African Nursing Council. In the clinical setting, students develop clinical skills which they will need as qualified primary health care practitioners. This is achieved through instruction and guidance by lecturers, mentors and clinical staff. However, the clinical learning environment can confront students with many challenges. During a qualitative study, purposive sampling selected nine students registered for Clinical Nursing Science, Health Assessment, Treatment and Care in an university. Students were placed in the clinical settings of Health Districts A and B in KwaZulu-Natal, South Africa. In-depth interviews were conducted and five themes emerged during data analysis. The themes related to shortage of staff, inadequate material/ non-human resources, lack of supervision in the clinical facilities, distant clinical facilities and insufficient practice in the clinical skills laboratory are the challenges that students experience while engaged in their WIL placement.